EVALUASI INOVASI KEMASAN TERHADAP PEMASARAN USAHA KRISPI PEYEK ”CRISPYEK” - Nurliani Nurliani; Corona Amarilis; Ida Rosada (AGRIBIOS, 2025)
UMKM play an important role in the Indonesian economy, especially in the traditional snack food sector. However, the main challenge faced by UMKM players is the suboptimal packaging design that affects product competitiveness in modern markets. This study aims to develop innovative packaging for “Crispyek” peyek products to enhance visual appeal, strengthen brand identity, and support marketing strategies. The method applied is a case study on a micro crispyek business as part of business plan implementation. The activities carried out include developing a business plan, conducting market surveys, designing packaging, and implementing online and offline marketing. The packaging innovation evaluation took place over a three-month period. The results of the activities showed an improvement in packaging quality through three stages of innovation: initial plain plastic packaging, followed by aluminum foil packaging with complete information, and finally, environmentally friendly packaging made from transparent thinwall material. Marketing strategies were implemented through social media (WhatsApp and Instagram), door-to-door methods, and word of mouth. Packaging innovation has proven to be effective in enhancing consumer appeal, maintaining product quality, and supporting environmental sustainability. Thus, packaging design development has become a strategic factor in strengthening the competitiveness of SMEs in the digital era.